STRATEGI MARKETING WISATA WEDDING SEBAGAI DESTINASI ALTERNATIF - Deden Acep Saefulloh; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2014)
This study aims to determine the marketing strategy applied to create a weddingtourism as an alternative destination in Bali, which some facts that must be considered tocreate a wedding tourism as an alternative destination in Bali. This research is taking placeon the island of Bali.This research is using a qualitative descriptive study that analyzed the data processingto describe and explain the circumstances in order to obtain a conclusion about the existingsituation and the impact of marketing strategies that runs in creating a wedding tourism as analternative destination in Bali.This research was carried out on 5 informants wedding who already running theirbusiness for more than 5 years. The conclusions of this study are: (1) It is difficult to find ofhuman resources which has reliable and professional capabilities due to wedding businessesrequire specialized knowledge while in Bali is less of institutions or special schools to learnabout wedding science. (2) There is still a lack of knowledge of the government about weddingtourism in Bali, incomplete information and less attractive website about the wedding whichavailable on www.disparda.baliprov.go.id so that was minimal information that obtained bywebsite visitors about wedding in Bali, and the lack of promotion by the Government relatingto the wedding tourism in Bali, including lack of wedding exhibition.Marketing strategy on wedding tourism obtained by observation and analysis using theSWOT analysis in order to see the strengths and weaknesses to determine a marketingstrategies in the future.Keywords: Tourism, Wedding, Wedding Tourism, Bali Wedding, Marketing Strategies, SWOTAnalysis